Reductions in systolic blood pressure achieved by hypertensiveswith three isometric training sessions perweek aremaintainedwith a single session perweek (2023)
Isometric handgrip or (wall) squat exercise performed three times per week produces reductions in systolic blood pressure (SBP) in adults with hypertension. We aimed to compare these interventions and the potential to retain benefits with one exercise session per week. We compared blood pressure changes following handgrip and squat isometric training interventions with controls in a randomized controlled multicentre trial in 77 unmedicated hypertensive (SBP ≥ 130 mmHg) adults. Exercise sessions were performed in the workplace and consisted of four repetitions—three sessions per week for the first 12 weeks (phase 1), and one session per week for the subsequent 12 weeks (phase 2). Office blood pressure (BP) was measured at baseline, post-phase 1 and post-phase 2. Post-phase 1, mean reductions in SBP were significantly greater in handgrip (–11.2 mmHg, n = 28) and squat (–12.9 mmHg, n = 27) groups than in controls (–.4 mmHg; n = 22) but changes in DBP were not. There were no significant within-group changes during phase 2 but SBP was 3.8 mmHg lower in the wall squat than the handgrip group—a small magnitude but clinically important difference. While both interventions produced significant SBP reductions, the wall squat appears to be more effective in maintaining benefits with a minimal training dose. The low time investment to achieve and retain clinically significant SBP reductions—42 and 12 min, respectively—and minimal cost, particularly of the wall squat, make it a promising intervention for delivery in public health settings.